Effect of Employee Wellbeing on Employee Engagement in Development Banks of Butwal Sub-Metropolitan City - Gautam, Niraj; Srivastava, Saurabh (Kalika Journal of Multidisciplinary Research, 2025)
The study intends to examine the effect of employee wellbeing dimensions-Conciliation, Confidence, Cultivation, Communication, and Compensation on employee engagement in development banks of Butwal Sub-metropolitan City. With the growing emphasis on human capital, understanding the factors that enhance engagement is vital for sustainable organizational performance. A total of 149 employees from development banks in Butwal were surveyed using a structured questionnaire based on a five-point Likert scale. The study adopted both descriptive and causal research designs. Purposive sampling was employed to select participants, and data were analyzed using correlation and regression techniques to assess the relationship between employee wellbeing factors and employee engagement. The findings revealed that among the various dimensions of employee wellbeing, Conciliation (work-life balance) and Compensation (financial and non-financial rewards) significantly influenced employee engagement. These two factors demonstrated a strong positive correlation and emerged as key predictors in the regression analysis, highlighting their role in promoting higher levels of engagement among banking employees. Development banks should prioritize initiatives that support work-life balance and offer competitive compensation packages to enhance employee engagement. By fostering a supportive environment that addresses both personal well-being and financial security, banks can improve job satisfaction, reduce turnover, and boost overall performance. HR policies must be reoriented to reflect the central role of conciliation and compensation in employee engagement strategies.